PENGARUH STRATEGI PEMASARAN, GAYA HIDUP, DAN PERILAKU KONSUMTIF TERHADAP KEPUASAN PELANGGAN PADA KEDAI SAERAH - Maharani, Ananda Aprilia (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2024)
This observation was conducted to see whether marketing strategy, lifestyle, and consumer behavior may influencecustomer satisfaction at Kedai Saerah Bandar Kidul Kediri. This study uses a quantitative research approach anda simple random sampling technique using the Slovin formula. From the calculation with the Slovin formula, a totalsample of 80 respondents was obtained. This study used multiple linear regression analysis. This study found thatmarketing strategy, lifestyle, and consumer behavior had a significant effect on customer satisfaction partially. Incontrast, simultaneously, marketing strategy, lifestyle, and consumer behavior significantly affected customersatisfaction.